2003
DOI: 10.1101/gad.1052803
|View full text |Cite
|
Sign up to set email alerts
|

A Serrate-expressing signaling center controlsDrosophilahematopoiesis

Abstract: The differentiation of Drosophila blood cells relies on a functional hierarchy between the GATA protein, Serpent (Srp), and multiple lineage-specific transcription factors, such as the AML1-like protein, Lozenge (Lz). Two major branches of Drosophila hematopoiesis give rise to plasmatocytes/macrophages and crystal cells. Serrate signaling through the Notch pathway is critical in the regulation of Lz expression and the specification of crystal cell precursors, thus providing a key distinction between the two li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
266
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(280 citation statements)
references
References 39 publications
11
266
3
Order By: Relevance
“…Among the hop Tum-l modifiers identified, several are known to interact with the JAK/STAT pathway or to be involved in blood or tumor formation. These include the human tumor suppressor nm23-H1 homolog abnormal wing discs (awd), Toll, PIAS, NURF301 and Serrate (Ser) (Supplementary Table 1) 7,15,[21][22][23][24] , supporting the specificity of this screen.A major class of E(Tum-l) genes identified in this screen encode proteins involved in chromatin modification. These include HP1, the histone H3-K9 methyltransferase Su(var)3-9, histone deacetylase (HDAC) Rpd3 and several other chromodomain-containing proteins ( Fig.…”
mentioning
confidence: 67%
“…Among the hop Tum-l modifiers identified, several are known to interact with the JAK/STAT pathway or to be involved in blood or tumor formation. These include the human tumor suppressor nm23-H1 homolog abnormal wing discs (awd), Toll, PIAS, NURF301 and Serrate (Ser) (Supplementary Table 1) 7,15,[21][22][23][24] , supporting the specificity of this screen.A major class of E(Tum-l) genes identified in this screen encode proteins involved in chromatin modification. These include HP1, the histone H3-K9 methyltransferase Su(var)3-9, histone deacetylase (HDAC) Rpd3 and several other chromodomain-containing proteins ( Fig.…”
mentioning
confidence: 67%
“…The functional relationship between Notch and Runx families during hematopoietic development was first indicated in Drosophila, in which Notch up-regulates the expression of a Runt family gene, Lozenge. 10 More recently, it was shown that a zebrafish Notchsignaling mutant mind bomb fails in the specification of definitive HSCs during embryogenesis, and that Runx1 is required for expansion of HSCs in the zebrafish AGM region sufficient to restore the HSC specification in the mind bomb mutant. 11 The data shown in the present study strongly indicate that the Notch-Runx pathway is conserved from invertebrates to mammals and that Runx1 locates at a very proximal position in the Notch1 signaling pathway during establishment of definitive hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 We thus first evaluated whether Notch activation results in up-regulation of Runx1 also in the mammalian system. When NIH3T3 cells were transiently transfected with Notch1 intracellular domain (NICD), which represents the constitutive active form of Notch1, the mRNA level of Runx1 increased (Table 1).…”
Section: Retroviral Expression Of Runx1 Rescues Hematopoietic Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSC provides niche signals to prohemocytes, which might stimulate renewal and block differentiation unless these cells are not needed in the circulatory system. PSC cells are determined early in Drosophila embryo development and have been characterized based on the expression of the Notch ligand Serrate (Lebestky et al, 2003), the transcription factors Collier/Knot (Col) and the homeotic Antennapedia gene (Morin-Poulard et al, 2013).…”
Section: Proteins In P Leniusculus Hematopoiesis -A Comparison With mentioning
confidence: 99%